1989
DOI: 10.1159/000238707
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxic Effects of a Pseudodisaccharide Aminoglycoside Antibiotic, Dactimicin, on the Inner Ears of Guinea Pigs

Abstract: The effect of dactimicin on the inner ear of guinea pigs was investigated by comparing it with the effects of ribostamycin, astromicin and amikacin. At doses of 200 and 400 mg/kg/day for 4 weeks, no pinna reflex loss was observed, but 2 animals receiving 400 mg dactimicin/kg/day showed unilateral loss of the outer hair cells in the cochlea and very scattered loss of the hair cells in the vestibular organ. At doses of 400 and 500 mg dactimicin/kg/day for 5 weeks, all surviving animals showed no abnormality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous studies of the ototoxicity of aminoglycoside antibiotics have demonstrated that the outer hair cells regularly disappear from the basal end to the upper turns of the cochlea. At the same time, the pinna reflex response regularly shows a loss from a high frequency (20 KHz) to a low frequency12, 15,16).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of the ototoxicity of aminoglycoside antibiotics have demonstrated that the outer hair cells regularly disappear from the basal end to the upper turns of the cochlea. At the same time, the pinna reflex response regularly shows a loss from a high frequency (20 KHz) to a low frequency12, 15,16).…”
Section: Discussionmentioning
confidence: 93%
“…In the case of cochlea damages, disap pearance of the outer hair cells extends from the basal end to the upper turns. At the same time, the pinna reflex responds to a loss of the auditory functions [1,2,8,9,25], The threshold of the pinna reflex re sponse decreases from 20 kHz to lower frequencies in guinea pigs receiving ami- noglycoside antibiotics. The threshold shift is closely related to morphological changes in the hair cells of the cochlea in histological findings [1,2,8,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, nephrotoxicity and ototoxicity as main adverse reactions were found for these an tibiotics [3,8,24]. Ototoxicity has been in vestigated in patients as well as experi mental animals such as rats, rabbits, guin ea pigs, dogs and monkeys [2,4,6,7,9,14,25,26]. Ototoxicity caused by amino glycoside antibiotics involves two types of impairment: (1) impairment of the vestibu lar functions characterized by loss of body equilibrium function, and (2) impairment of hearing characterized by morphologi cal changes in the cochlear hair cells [2,4,5,7,11,16,21].…”
Section: Introductionmentioning
confidence: 99%